SIFAT PULP KIMIA-TERMOMEKANIK (CTMP) KA YU MANGIUM (Acacia mangium Willd) DARI BERBAGAI TINGKAT UMUR - Rena M; Siagian Siagian; Han Roliadi; Togar Hendrik Martua (Jurnal Penelitian Hasil Hutan, 2001)
This investigation deals with the assessment of mangium (Acacia mangium Willd.) wood plantation of various maturities for the manufactureof chemi-thermo-mechanical pulp (CTMP) with varying chemical (alkali) concentrations. The properties of CTMP examined were those related to its possibility for newsprint. The ages consisted of three levels (i.e. 6, 7 and 10 years) at which the respective mangium stands were normally harvested from their first rotation. Three ages groups, of mangium were felled for obtaining wood samples. Afterwards, the mangium woods were chipped for further investigation. The alkali concentrations for pre-pulping (chip- softening) stage were consecutively 2, 4, 6, and 8 percent. In the Asplund refiner, the softened chips underwent a 15 minute pre-steaming at 5 psi and then fiberized into pulp for 3 minutes in the Asplund refiner. The resulting pulp were determined for their yield, and further bleached by using peroxyde in 2 stages. The bleached pulps were also examined of their yield, and subsequently made into handsheet at the targeted grammage (50 gram per sq.m) for testings of their actual grammage, strength and optical properties.Data analysis reveals that different wood ages and varying alkali concentrations did not contribute significant effect on their bleached pulp yield. The pulp yields were relatively high in the range of 60-75 percent. The hand-sheets of pulp in terms of its grammage, ranged from 43.0 to 51.6 g/m2. These could satisfy the SNI (Indonesian National Standards) requirements for newsprint. The thicknesses of pulp sheets, which were above 0.10 mm, did not meet the newsprint pulp standard quality requirement. Physical properties of mangium CTMP as described by their tensile, and tear index were correlated positively with wood age. On the contrary, these properties were not affected by alkali concentrations. Further, the different wood maturities brought about significant changes in pulp brightness; and so did the alkali concentration, whereby the brightness was affected negatively. Further, the opacity of the pulp sheet was not affected by wood maturities and alkali concentrations.Wood of 10 years old and with alkali concentration at 2 percent were found to be the optimum treatment combination for its application in the manufacture of CTMP for newsprint. The grammage, thickness, physical, and optical properties of the resulting CTMP, satisfy the SNI requirement for newsprint.